Establishment of resource-saving modes of irrigation pumps - Glovatskiy Oleg; Ergashev Rustam; Sadiev Umid; Rashidov Jaloliddin; Musaev Sharof; Boboeva Gulmira (E3S Web of Conferences, 2023)
The article presents the results of a study obtained in the process of testing the flow path of modernized centrifugal pumps. The authors proposed the device of new elements based on the calculation of the flow limited only by the side walls. The purpose of this work is to change and refine the calculations of the indicators of the modes of pumping units and the features of the performance of modern vane pumps. They are developed on the basis of the results of a large number of tests carried out by the authors of pump assemblies and operational surveys of irrigation pumping stations in Uzbekistan. The determination of the economically viable duration of the period of operation of pumping units, taking into account changes in energy characteristics and resource-saving operating technologies, was refined when measuring the efficiency of the upgraded pump D2000-100 under various operating modes. The creation of resource-saving methods of operation of pumping units that reduce or eliminate the intensity of cavitation-abrasive wear, including those based on taking into account changes in flow rates in the inter-blade channels of the impeller, is shown in the corresponding characteristics of the upgraded pump.